2021
DOI: 10.1097/01.naj.0000803188.10432.e1
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination: A Concept Analysis

Abstract: Care coordination is both a well-known concept discussed in a wide range of multidisciplinary health care literature and a familiar nursing role in clinical practice; however, the definition of care coordination lacks role clarity across disciplines and within the nursing profession. Despite variations, defining factors of care coordination practice exist; however, role ambiguity limits the effective implementation of evidence-based care coordination in practice and policy. Following Walker and Avant's eight-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Past concept analyses of care coordination included communication as an essential attribute 1,2 . However, specific systems of communication used in the context of school‐based care coordination have not been fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…Past concept analyses of care coordination included communication as an essential attribute 1,2 . However, specific systems of communication used in the context of school‐based care coordination have not been fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Care coordinators are primarily nurses who work with patients to address their problems with chronic health issues, including mental and social concerns that can affect their health and care. 4 Care coordinators can provide an array of services, including facilitating communication between providers and patients, educating patients on chronic disease and self-management, managing medication complexities, making referrals for medical or social resources, and coaching patients on health behaviors. 1,2 Care coordination is most often studied from a health system and provider point of view focusing on effectiveness of outcomes and care practice issues.…”
mentioning
confidence: 99%
“…It is a method for addressing care fragmentation and improving health outcomes, as well as reducing high utilization and costs of care 2,3. Care coordinators are primarily nurses who work with patients to address their problems with chronic health issues, including mental and social concerns that can affect their health and care 4. Care coordinators can provide an array of services, including facilitating communication between providers and patients, educating patients on chronic disease and self-management, managing medication complexities, making referrals for medical or social resources, and coaching patients on health behaviors 1,2.…”
mentioning
confidence: 99%
“…To achieve this, the authors suggested a consensus-based articulation of the data elements of care coordination 1 . A recent concept analysis operationally identified those information needs 2 (p37) :…”
mentioning
confidence: 99%